Desenvolvimento e caracterização de copolímeros produzidos a partir dos monômeros anilina e 4-aminofenol para aplicação em plataforma de biossensores - Lacerda, Ariadne Fernandes (2020)
Modified electrodes are a simple and cheap alternative for optimization of classical electrodes by improving sensitivity and selectivity and thus opening greater possibilities of applications. Modification by electropolymerization is a technique based on the use of conductive or permeable polymers in the electrolyte support and the species of interest to cover the electrode surface, with the objective of increasing the electrochemical response, protecting the electrode surface from impurities, blocking interferents., immobilize biomolecules, incorporate mediators and provide biocompatibility. Polyaniline (PAni), sintetized by the aniline monomer, has a promising conductive character for application, besides good thermostability, low price, high yield and ease of synthesis by chemical and electrochemical routes in various organic solvents or even in aqueous. 4-Aminophenol has in its structure two different substituent groups (-NH2 and -OH) linked in an aromatic ring, then it can be a great candidate for biomolecule binding sites. The present work aimed to study the parameters of production of a copolymer formed by these two monomers, such as their characterization via electrochemical, infrared and scanning electron microscopy. Different variables were used between the copolymers in the proporciono of monomers in solution and different potential ranges in cyclic voltammetry for electropolymerization. The most promissor copolymers were submitted to probe and probe / target detection test using direct and indirect methodologies wit polyGA and polyCT. The study was able to determine and characterize a specific methodology for the development of the EG / Poly (4-aminophenol-aniline) platform which presented more satisfactory results than the EG / polyaniline and EG / poly (4-aminophenol) platforms for the future purpose. of application in the development of biosensors.